2022
DOI: 10.1101/2022.09.17.508285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STAT1 is required to establish but not maintain IFNγ-induced transcriptional memory

Abstract: Exposure of human cells to interferon-γ (IFNγ) results in a mitotically heritable yet reversible state called long-term transcriptional memory. We previously identified the clustered GBP genes as strongly primed by IFNγ. Here we discovered that in primed cells, both interferon-responsive transcription factors STAT1 and IRF1 target chromatin with accelerated kinetics upon re-exposure to IFNγ, specifically at promotors of primed genes. Priming does not alter the degree of IFNγ-induced STAT1 activation or nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Signal transducer and activator of transcription 1 (STAT1) belongs to the STAT protein family and mediates cellular responses to the Janus kinase (JAK)-signal, interferons (e.g., IFN-γ), IFN-stimulated genes (ISG) and relative modulators (e.g., KITLG/SCF, IRF-9), and the dysfunction of STAT1 commonly causes diverse immune dysregulation phenotypes [40][41][42][43]. For example, Grohmann et al put forward contribution of obesity-associated hepatic oxidative stress upon the pathogenesis of NASH in C57BL/6 mice via increasing STAT1/STAT3 signaling and inactivating the T cell protein tyrosine phosphatase (TCPTP) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Signal transducer and activator of transcription 1 (STAT1) belongs to the STAT protein family and mediates cellular responses to the Janus kinase (JAK)-signal, interferons (e.g., IFN-γ), IFN-stimulated genes (ISG) and relative modulators (e.g., KITLG/SCF, IRF-9), and the dysfunction of STAT1 commonly causes diverse immune dysregulation phenotypes [40][41][42][43]. For example, Grohmann et al put forward contribution of obesity-associated hepatic oxidative stress upon the pathogenesis of NASH in C57BL/6 mice via increasing STAT1/STAT3 signaling and inactivating the T cell protein tyrosine phosphatase (TCPTP) [32].…”
Section: Discussionmentioning
confidence: 99%
“…This transcriptional adaptation is facilitated by both ‘cis-acting’ factors such as DNA methylation or histone modifications, which may be locally inherited through the cell cycle, and by ‘trans-acting’ factors such as transcription factors that re-initiate and/or maintain the signal even in its absence 263. Not surprisingly, trained immunity is regulated by the epigenome.…”
Section: Mechanisms Of Tissue Adaptationmentioning
confidence: 99%
“…This chromatin opening is facilitated by H3K4me3 marks and can be retained for a year,25 28 illustrating the importance of epigenetic mechanisms mediating cellular innate immune memory 267. This epigenetically driven long-term transcriptional memory is observed on exposure to inflammatory cytokines such as TNF and IFNs even in non-classical immune cells 31 263 268…”
Section: Mechanisms Of Tissue Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to discover the mechanism driving transcriptional memory at GBP genes. We previously found that trans-acting factors including upstream IFNγ signalling, JAK kinase activity, Polymerase II occupancy and activation of the key downstream transcription factor STAT1 are not the carriers of long-term memory 10 . Similarly, cis-acting chromatin features that are associated with active gene expression, including an increase in chromatin accessibility, H3K27 acetylation and H3K36 trimethylation are only transiently associated with GBP genes but return to baseline levels upon loss of expression 8 .…”
Section: Specific Active Chromatin Modifications Are Established Duri...mentioning
confidence: 99%